Psychosocial functioning in adolescents with perinatal HIV infection receiving highly active antiretroviral therapy - Orawan Louthrenoo (2018)
Background: With effective highly active antiretroviral therapy (HAART), perinatally HIV-infected children are living longer through adolescence. Methods: We conducted a cross-sectional study of perinatally HIV-infected adolescents, aged 11 to 18 years. Demographically matched controls were also enrolled. The adolescents completed the Youth Self-Report (YSR), while the caregivers filled out the Child Behavior Checklist (CBCL), to determine emotional and behavioral problems. Results: The sample included 50 HIV-infected adolescents and 56 controls. The internalizing problem scores from the YSR were significantly higher in the HIV-infected group than those in the control group (13.76 versus 9.95, P .02). The total competence scores, from both the self-report and the caregiver report in the HIV-infected group, were significantly lower than those of the control group (P .005 and .001). Conclusion: Although HAART has prolonged the survival of HIV-infected children, they remain at increased risk of psychosocial problems as well as impaired social functioning.